Status Kesehatan Lansia Yang Bekerja - agus setyo utomo (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2017)
Abstract: The life expectancy of the population in East Java increased until the period 2015-2020 to73.2 years. Along with the increase of age followed by a decline in physical ability so it is not uncommonto health concerns felt by the elderly. However, many elderly are still working to make ends meet. Thepurpose of this study to analyze the relationship of elderly activity useful (load activity, physical mobility,social interaction) with health status. This study was cross sectional study. The population in thisstudy were all elderly people who work some 215 people. While the sample is mostly elderly people whowork by simple random sampling technique sampling and sample size of 140 respondents. This studyused logistic regression analysis with the results of the independent variables jointly affect the healthstatus of respondents with significant value Workload (Sig. = 0.000), Mobility (Sig. = 0.010) andInteraction (Sig = 0.000)). Selection of work for the elderly should not have a heavy workload, there isno competition and deadlines.